Efficiency enhancement of dye-sensitized solar cell based gel polymer electrolytes using Poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate)/tetrapropylammonium iodide. (1st March 2019) - Farhana, N.K.; Ramesh, S.; Ramesh, K.
Abstract: Due to liquid electrolyte limitation in dye sensitized solar cells (DSSCs), GPEs were prepared and optimized. Poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate), P(VB-co-VA-co-VAc) acted as host polymer and tetrapropylammonium iodide, TPAI as dopant salt. The prepared gel polymer electrolytes (GPEs) with different TPAI salt content were characterized using electrochemical impedance spectroscopy, Fourier transform infrared spectroscopy and X ray diffractogram. An optimum ionic conductivity of 1.93 mS cm −1 was obtained with 40 wt% of TPAI salt added along with the lowest activation energy of 0.064 eV. Temperature dependence ionic conductivity behaviour of GPEs were studied and found that the systems obeyed the Arrhenius behaviour in the temperature range of 303–373 K. The dielectric results studies showed typical behaviour of both ε ′ and ε ′ ′ inversely proportional to frequency and directly proportional to temperature. Structural studies of GPEs were performed using XRD and FTIR and confirmed the existence of complexation of P(VB-co-VA-co-VAc) and TPAI salt. GPEs were used to assemble dye sensitized solar cells (DSSCs). The power conversion efficiency of 4.615% achieved with a maximum short circuit current density (Jsc ) of 13.585 mA cm −2, open circuit voltage (Voc ) of 0.678 V and fill factor of 50.1% at 40 wt% TPAI salt under A.M 1.5 (100 mW cm −2 ) illumination.